“O açaí nosso de cada dia”: formas de consumo de frequentadores de uma feira amazônica (Pará, Brasil) 1 - Flavio Henrique Souza Lobato; Voyner Ravena-Cañete (Ciências Sociais Unisinos)
This article aimed to identify how many are the forms of consumption of acai berry and how important is the fruit in Amazonian contexts, such as the Igarapé-Miri City (PA), by the vision of the city fair. This city was chosen as a research local, because it is a locality where açai consumption is still seen as traditional and for the reason that it is considered the “Açaí World Capital”. The methodological pathway built to reach the proposed goal was established from a qualitative approach, with bibliographical, documentary and field research. From a procedural and methodological point of view, data collection instruments were used, followed by of direct observations in the Igarapé-Miri Market and Trade Complex, photographic records, informal conversations and interviews with market participants and açaí consumers. The results obtained allowed a understanding that the açaí in this city transpasses the sine qua non role of food for the human living, comprising, in fact, a cultural element of the daily life of the inhabitants of that city. It is present and represented by / in multiple and different ways, it has multifaceted functions and forms of consumption still considered traditional.